Japan 2050 Low Carbon Navigator: Possible application for assessing climate policy impacts. (November 2019) - Moinuddin, Mustafa; Kuriyama, Akihisa
Abstract: This paper explores Japan's energy and emissions-related choices up to 2050 using the Japan 2050 Low Carbon Navigator (Low Carbon Navigator), an energy and emissions scenario simulation tool based on the 2050 Pathways Calculator model. Using illustrative examples and scenarios, the paper demonstrates some unique features of the Low Carbon Navigator that enables assessment of the policy impacts relating to Japan's 3E + S (economic efficiency, energy security, environmental protection and safety) objectives. Five representative energy scenarios are developed to simulate the pathways to attain the emissions reduction targets. Simulation results from these five energy scenarios show that climate and energy policy measures on the energy supply side, such as the decision on whether or not to revive Japan's nuclear power plants, or on building new coal-fired plants, will significantly affect the country's emissions-related targets and energy security. The results show the trade-off between economic efficiency and environmental protection as well as energy security and safety. Furthermore, this paper highlights that the choice of future society scenarios that influence the size of the country's GDP, economic structure and resource dependence is also a crucial factor that affects future GHG emissions levels. Although the Low Carbon Navigator is not able to reflect all the users' assumptions, it can serve as an important tool to generate awareness among researchers, policymakers and the general public, and provides a platform for engaging debate on Japan's energy and emissions choices. Highlights: This paper explores Japan's the basic energy policy of "3E + S" using the Japan 2050 Low Carbon Navigator. The results show the trade-off between economic efficiency and environmental protection as well as energy security and safety. The choice of future society scenarios influencesJapan's economy and resource dependence, which affects future emissions.